RESIDU LOGAM BERAT DALAM DAGING SAPI YANG DIPELIHARA DI TEMPAT PEMBUANGAN SAMPAH AKHIR - Agus Suyanto; Sri Kusmiyati; Ch Retnaningsih (Universitas Muhammadiyah Semarang, 2010)
Food safety precautions sufficient attention in considering the many cases of food contamination, one of which is heavy metal contamination of beef shepherd in final disposal facility). Pollution cows by heavy metals can cause health hazards to humans. The research aims to determine the content of heavy metals (Hg, Cd, Co, Zn, Pb and As). Design research is a survey study with comparisons of meat from cows raised form final disposal and outside. Heavy metal residues form final disposal that exceed the quality standard : a) Zinc 69.50 ppm (Semarang), 47.60 ppm (Surakarta) 46.41 ppm (Sragen). b) Cadmium 0.06 ppm (Surakarta), TPA 0.06 ppm (Semarang). Heavy metal residues form outside discovered the existence of heavy metals in excess of the quality standard: a) Zinc 52.0 ppm (Sragen), 51.4 ppm (Surakarta), and 47.63 ppm (Semarang). b) Cadmium from Semarang 0.13 ppm. Heavy metals content Pb, Cu, Hg, Co, and As were below the quality standard. The presence of heavy metals content in cows that exceeds a warning threshold of awareness of the need to improve security. Key words: heavy metals, cows, final disposal facility